2018
DOI: 10.1101/508358
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Speech Fine Structure Contains Critical Temporal Cues to Support Speech Segmentation

Abstract: 1Segmenting the continuous speech stream into units for further perceptual and linguistic 2 analyses is fundamental to speech recognition. The speech amplitude envelope (SE) has 3 long been considered a fundamental temporal cue for segmenting speech. Does the 4 temporal fine structure (TFS), a significant part of speech signals often considered to 5 contain primarily spectral information, contribute to speech segmentation? Using 6 magnetoencephalography, we show that the TFS entrains cortical oscillatory respo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 74 publications
0
8
1
Order By: Relevance
“…Our previous work (Teng, Tian, Doelling, & Poeppel, 2018b) showed that the onset responses were modulated by different frequency modulation spectra even though the same ramping windows were added to the stimuli of different 1/f modulation spectra. This interesting difference between the current experiment and Teng et al, 2018 suggests that not only the shape of amplitude envelopes but also spectral details of sounds significantly modulate auditory evoked responses (Oganian & Chang, 2018;Teng, Cogan, & Poeppel, 2018a).…”
Section: Onset/offset Responses and Induced Power Do Not Significantlcontrasting
confidence: 88%
“…Our previous work (Teng, Tian, Doelling, & Poeppel, 2018b) showed that the onset responses were modulated by different frequency modulation spectra even though the same ramping windows were added to the stimuli of different 1/f modulation spectra. This interesting difference between the current experiment and Teng et al, 2018 suggests that not only the shape of amplitude envelopes but also spectral details of sounds significantly modulate auditory evoked responses (Oganian & Chang, 2018;Teng, Cogan, & Poeppel, 2018a).…”
Section: Onset/offset Responses and Induced Power Do Not Significantlcontrasting
confidence: 88%
“…The representation of speech in the brain is often examined by measuring the alignment of rhythmic brain activity to the acoustic envelope of the signal ( Ahissar et al., 2001 ; Ding et al., 2014 ; Giraud and Poeppel, 2012 ; Gross et al., 2013 ; Kayser et al., 2015 ; Oganian and Chang, 2019 ; Teng et al., 2019 ; Teoh et al., 2019 ). To quantify this alignment, many studies rely on the overall or broadband acoustic envelope, which describes the amplitude fluctuation of the signal across the full spectral range and which provides a convenient and low-dimensional representation for data analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A higher reconstruction accuracy between EEG responses and the speech envelopes was found in the delta and theta bands than that in the higher frequency bands, which was consistent with the literature (e.g., Ding and Simon, 2013 ; Di Liberto et al, 2015 ). However, speech features in the time and spectral domain could all affect the speech perception and corresponding cortical responses (e.g., Biesmans et al, 2016 ; Teng et al, 2019 ). Future studies could systematically analyze how cortical responses track the speech features at different auditory-inspired narrow bands to better simulate the processing in the auditory peripheral and central systems.…”
Section: Discussionmentioning
confidence: 99%